Here's the question you clicked on:
Sabrena
Solve this equation. (x-5)(4x+3)=0. Totally went blank. Any Help
|dw:1355012579897:dw| Can someone help me here...They have went over so many things that I am drawing a blank.
so since the product of both brackets is 0, we could say (x-5)=0 and (4x+3) =0
\[(x-5)(4x-3)=0\] This is the original equation. So, either \[(x-5)=0\] or \[(4x-3)=0\]. So, \[x=5\] and \[4x=3\]. Simplify: \[x=5\] and \[x=\frac{ 4}{ 3 }\]. Final answer: \[\left\{ 5,\frac{ 4 }{ 3 } \right\}\].
Sorry, I just noticed it is 4x+3, just do the same thing, but with a negative sign.